Contribuições de projetos integradores em uma escola pública: desenvolvimento das competências socioemocionais - Lúcia Cristina Monteiro Cruz (2023)
The development of socio-emotional skills has become a legal requirement in curricula, to ensure the comprehensive training of students. Therefore, the main objective of this thesis was to understand the contributions of integrative workshop projects of a public school in Contagem of sixth grade students socio-emotional development skills. To achieve this purpose, three studies were carried out that allowed a qualitative and quantitative characterization of the object of study. Initially, the students filled out a sociodemographic questionnaire and answered the Senna Instrument, to map the sociodemographic profile and assess socioemotional skills level respectively. We collected quantitative data to assess their scores on the five socio-emotional competencies before studying the workshop content. Qualitative data were obtained through observations and interviews with educators. Observations were carried out trough workshops at three sixth grade classes. After observing the workshops, a semi- structured interview was conducted with a focus group represented by the educators involved in the workshops at three sixth grade classes. The quantitative results express differences in the participants' scores in the five socio-emotional competencies, thus suggesting the presence of potential possibilities for improvement in the development of competencies. Furthermore, the results of the qualitative data indicate that, in the integrative workshop projects, strategies are adopted aimed at covering the skills that have different developments demonstrated in the quantitative data. Furthermore, the educators reported, during the interview, that they realize that their practices provide opportunities for reflections on socio-emotional skills. This study may contribute to reflections on public policies and restructuring of educational curricula aimed at the development of socio-emotional skills.